Cover Picture: Ambient Pressure Photoemission Spectroscopy Reveals the Mechanism of Carbon Soot Oxidation in Ceria‐Based Catalysts (ChemCatChem 17/2016). Issue 17 (30th August 2016) - Soler, Lluís; Casanovas, Albert; Escudero, Carlos; Pérez‐Dieste, Virginia; Aneggi, Eleonora; Trovarelli, Alessandro; Llorca, Jordi
Abstract : The Front Cover shows a representation of the ALBA synchrotron, where near ambient pressure photoelectron spectroscopy was performed to study the surface/subsurface of ceria and ceria‐zirconia catalysts for removing soot from combustion engines. In their Communication, L. Soler et al. identified two cooperative routes, one occurring at the ceria–soot interface with formation of O vacancies and Ce III, and another at the surface of soot mediated by superoxide species resulting from the reaction between O2 gas and O vacancies (drawing by Javier Sánchez Ríos, javier. sanchezrios.1978@ieee.org). More information can be found in the Communication by L. Soler et al. onpage 2748 in Issue 17, 2016 (DOI:10.1002/cctc.201600615 ).